Ulama in The Perspective of The Qur'an: Roles, Responsibilities, and Teachings of Islam - Ta’wil; Yusuf, Muh.; Haddade, Hasyim (Manunggal Halim Jaya, 2025)
This study explores the concept, roles, and responsibilities of ulama from the perspective of the Qur’an, highlighting their theological significance and sociocultural function in both classical and contemporary Islamic thought. Utilizing a qualitative approach based on systematic literature review, the research draws upon selected Qur’anic verses, classical tafsir, and modern scholarly works to identify core attributes of ulama, including their intellectual authority, moral integrity, and social leadership. The study aims to provide a comprehensive understanding of how the Qur’an frames the position of ulama not only as religious teachers but as ethical agents entrusted with the preservation and contextualization of divine guidance. The findings reveal that the Qur’an emphasizes the interconnectedness between knowledge (‘ilm), piety (taqwa), and wisdom (hikmah), and positions the ulama as individuals who embody these principles in guiding the Muslim community. Furthermore, the study discusses how the function of ulama has evolved in response to modern challenges such as globalization, digital media, and ideological fragmentation. The research concludes that a Qur’an-based understanding of ulama offers a timeless yet dynamic model for religious leadership, capable of addressing both spiritual and societal needs in contemporary Muslim societies. The study also provides theoretical and managerial implications for Islamic education institutions, policy-makers, and religious authorities seeking to enhance the role of ulama in the 21st century.